Extremely High Electron Mobility in GeSn Epitaxial Films by Chemical Vapor Deposition - Kai‐Ying Tien; Yen‐Yang Chen; Chia‐You Liu; Hsiang‐Shun Kao; Jiun‐Yun Li (Advanced Electronic Materials)
Abstract Direct‐bandgap germanium‐tin (GeSn) has attracted much interest for high‐performance optoelectronic and electronic device applications. However, the transition from indirect bandgap to direct bandgap in GeSn epitaxial films and the effects on the electron transport properties are not fully understood. In this work, the electron populations and transport properties are investigated in high‐quality n‐GeSn films epitaxially grown using chemical vapor deposition under different strain conditions. Hall measurements are performed to characterize the effective density and mobility in the n‐GeSn films at temperatures from 300 to 4 K. Very high electron mobilities up to 6,200 and 1,500 cm2V−1s−1 are achieved in the strain‐relaxed Ge0.88Sn0.12 film at 50 and 300 K, respectively, due to the increased electron population in the direct Γ‐valley. The band structures are also simulated using the empirical pseudopotential method (EPM) to calculate the electron density in n‐GeSn films. The simulation results support the experimental data and strongly suggest that applying more tensile stress on the GeSn films or increasing the Sn fraction in the strain‐relaxed GeSn films is critical to achieving direct‐bandgap characteristics.